2005
DOI: 10.1007/s00425-005-1504-x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic transfer of α-L-arabinopyranosyl residues to exogenous 1,4-linked β-D-galacto-oligosaccharides using solubilized mung bean (Vigna radiata) hypocotyl microsomes and UDP-β-L-arabinopyranose

Abstract: A single alpha-L-arabinopyranosyl (alpha-L-Arap) residue was shown, by a combination of chemical and spectroscopic methods, to be transferred to O-4 of the nonreducing terminal galactosyl (Gal) residue of 2-aminobenzamide (2AB)-labeled galacto-oligosaccharides when these oligosaccharides were reacted with UDP-ss-L-arabinopyranose (UDP-ss-L-Arap) in the presence of a Triton X-100-soluble extract of microsomal membranes isolated from mung bean (Vigna radiata, L. Wilezek) hypocotyls. Maximum-(1-->4)-arabinopyrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
(34 reference statements)
4
20
0
Order By: Relevance
“…2D). We have also shown that the arabinan side chains have an average DP of 6 in the RG-I isolated from 3-d-old mung bean hypocotyls (Ishii et al, 2005c). The availability of a facile assay for ArafT activity provides an opportunity to investigate arabinan synthesis in great detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2D). We have also shown that the arabinan side chains have an average DP of 6 in the RG-I isolated from 3-d-old mung bean hypocotyls (Ishii et al, 2005c). The availability of a facile assay for ArafT activity provides an opportunity to investigate arabinan synthesis in great detail.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous layer was freeze dried. The residue was dissolved in 75% CH 3 CNwater (v/v) and separated by normal-phase HPLC (Ishii et al, 2005c). The purified product was analyzed by LC-ESI-mass spectrometry and 1 H-NMR spectrometry (Ishii et al, 2005c).…”
Section: Analysis Of Enzymatically Formed Oligosaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…A single Arap residue was attached to galacto-oligosaccharide ( Fig. 3B) (17). From these results we speculated that Araf residues are formed from UDP-Araf, not UDP-Arap.…”
Section: Is a Sugar Donor For Biosynthesis Of Arabinofuranosyl Residuesmentioning
confidence: 78%